Inflammatory Markers in Rheumatoid Patients and Cardiac Function: Insights from an Iranian University Hospital - Omidi, Fatemeh; Delkash, Parisa (Novelty in Biomedicine, 2024)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder associated with increased cardiovascular morbidity and mortality. This study investigated the association between RA inflammatory markers, such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and various cardiac function parameters. Materials and Methods: A cross-sectional study involved 71 patients diagnosed with RA at Imam Hossein Hospital in Tehran, Iran. Cardiac function parameters, including left ventricular end-diastolic diameter (LVDD), left ventricular end-systolic diameter (LVDS), left ventricular ejection fraction (EF), E/A ratio, septal e’ velocity, left atrial (LA) area, and LA size, were assessed using echocardiography. The correlation between RA inflammatory markers and cardiac function parameters was analyzed using Pearson correlation coefficients. Multiple linear regression models were employed to further explore these associations. Statistical analyses were performed using SPSS Statistics version 26. Results: Among the cardiac function parameters assessed, only LA size significantly correlated with RA inflammatory markers (ESR-CRP) (p = 0.034). However, LVDD, LVDS, EF, and E/A ratios did not exhibit significant correlations. Septal e’ velocity notably showed a weak positive correlation with inflammatory markers. Conclusion: Our findings suggest a potential link between systemic inflammation in RA and cardiac remodeling, particularly affecting LA size. This highlights the importance of monitoring cardiac function parameters, especially LA size, in RA patients to identify individuals at higher risk of cardiovascular complications. Further research is warranted to elucidate this association’s underlying mechanisms and clinical implications.